Music radio the great performers and programs of the 1920s through early 1960s - Cox, Jim 1939- (McFarland, 2005)
"This work encompasses the range of musical programming from the early 1920s to the early 1960s. Jazz, country, classical, gospel, pop, big band, western, and semi-classical forms are covered, as are the vocalists, instrumentalists and disc jockeys who made them available to listeners"--Provided by publisher.
"This work encompasses the range of musical programming from the early 1920s to the early 1960s. Jazz, country, classical, gospel, pop, big band, western, and semi-classical forms are covered, as are the vocalists, instrumentalists and disc jockeys who made them available to listeners"--Provided by publisher.
Includes bibliographical references (p. 341-344) and index
Keywords: Geschichte 1900-2000; Geschichte 1920-1965; Musik; Radio and music -- United States; Radio programs, Musical -- United States; Music -- United States -- 20th century -- History and criticism; Musicians -- United States; Disc jockeys -- United States; Hörfunk; USA